Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 7 - Exponential Functions - 7.3 Logarithms and Their Derivatives - Exercises - Page 343: 30


$$ y'= \ln t.$$

Work Step by Step

Since $ y=t\ln t-t $, then by using the product rule, we have $$ y'=\ln t +t (1/t) -1=\ln 1-1=\ln t.$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.